Peculiarities of thermoannealing in n-Si and n-Ge crystals with oxygen impurity - Baranskii, P.I.; Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
. Investigated in this work were changes in the concentration of charge carriers ne and their mobilities u, which occur under the influence of thermoannealing of n - Si and n - Ge crystals grown by the Czochralski method. Thermoannealing of n - Si samples was carried out both at 450 °C and 650 °C. The results of the influence of twostage (combined) thermoannealing have been presented. In the first series of experiments, the annealing was performed at 450 °C with varied duration (from 5 to 45 h) at the beginning, and then it was carried out for 40 hours at 650 °C. The second series of experiments was as follows: the annealing at 450 °C for 45-hour duration, then the annealing at 650 °C, which was carried out for various periods of time (5, 10, 20, 45, 66 hours). The observations for changes of ne and u were carried out both at the temperature 300 and 77 K. It is ascertained that changing the main parameters (ne and u) in n  Ge As heavily doped single crystals, as a result of the series of thermoannealings (duration 30 min in each case) within the temperature range from 540 to 900 °C, is non-monotonous due to transformation of the thermodonors TD - I into TD-II .